Staphylococcal and Streptococcal Superantigen Exotoxins - Spaulding, Adam R. (American Society for Microbiology, 2013)
SUMMARY: This review begins with a discussion of the large family of Staphylococcus aureus and beta-hemolytic streptococcal pyrogenic toxin T lymphocyte superantigens from structural and immunobiological perspectives. With this as background, the review then discusses the major known and possible human disease associations with superantigens, including associations with toxic shock syndromes, atopic dermatitis, pneumonia, infective endocarditis, and autoimmune sequelae to streptococcal illnesses. Finally, the review addresses current and possible novel strategies to prevent superantigen production and passive and active immunization strategies.